Measuring the depth of reflection in reflective supervision/consultation sessions: Initial validation of the Reflective Interaction Observation Scale (RIOS). Issue 2 (13th August 2021) - Meuwissen, Alyssa S.; Watson, Christopher
Abstract: Research on reflective supervision and reflective consultation (RS/C) is limited, and has primarily relied on self‐report measures and qualitative interviews. To our knowledge, no measures currently exist which provide a way to observationally measure what occurs during an RS/C session. Thus, the Reflective Interaction Observation Scale (RIOS) was created as a way to more objectively measure the quality of RS/C. This study sought to provide initial evidence around the reliability and validity of the RIOS through a sample of child welfare workers ( N = 40) who participated in six online group reflective consultation sessions and completed self‐report surveys after their first and last session. The RIOS was used to code the first and last session each participant attended. Results showed that in this sample the RIOS Essential Elements had good variability and strong reliability. The data suggested that the five Elements could be condensed into three subscales, two of which showed significant change over time. The Self Openness subscale showed concurrent validity with existing self‐report measures of RS/C. Results suggest that the RIOS shows promise as a measure that could contribute to a more rigorous evidence base for the practice of RS/C. Resumen: La investigación acerca de la supervisión con reflexión y la consulta con reflexión (RSC) es limitada y primariamente ha confiado en medidas de auto reporte y entrevistas cualitativas. Hasta donde alcanza nuestro conocimiento, no existen actualmente medidas que ofrezcan una manera de medir desde la perspectiva observacional lo que ocurre durante la sesión de RSC. Por tanto, la Escala de Observación de la Interacción con Reflexión (RIOS) se creó como una manera de medir más objetivamente la calidad de RSC. Este estudio se propuso proveer evidencia inicial acerca de la confiabilidad y validez de RIOS por medio de un grupo muestra de trabajadores den el campo del bienestar infantil (N = 40) que participaron en seis sesiones de grupo en línea sobre la consulta con reflexión y completaron encuestas de auto reporte después de su primera y última sesiones. RIOS se usó para codificar la primera y la última sesión a la que cada participante asistió. Los resultados muestran que en este grupo muestra los Elementos Esenciales de RIOS tuvieron buena variabilidad y una fuerte confiabilidad. La información sugiere que los cinco Elementos Esenciales pueden ser agrupados en tres subescalas, dos de las cuales muestras un cambio significativo con el pasar del tiempo. La escala de Auto Apertura mostró una validez concurrente con medidas existentes de auto reporte de RSC. Los resultados sugieren que RIOS es una medida prometedora que puede contribuir a una más rigurosa base de evidencia para la práctica de RSC. Résumé: Les recherches sur la supervision réflective et la consultation réflective (RSC) sont limitées et ont avant tout reposé sur des mesures d'auto‐évaluation et des entretiens qualitatifs. A notre connaissance il n'existe actuellement aucune mesure qui offre une manière de mesurer par observation ce qui se passe durant une session de RSC. Par conséquent l'Echelle d'Observation de l'Interaction Réflective (abrégé RIOS en anglais) a été créée en tant que moyen de mesurer par observation la qualité de la RSC. Cette étude s'est donné pour but d'offrir des résultats préliminaires sur la fiabilité et la validité de RIOS au travers d'un échantillon d'employés de la protection de l'enfance (N = 40) ayant participé à des sessions de consultation réflective de groupe en ligne et rempli des questionnaires d'auto‐évaluation après la première et la dernière session. RIOS a été utilisée pour coder la première et la dernière session à laquelle chaque participant a participé. Les résultats montrent que dans cet échantillon les éléments essentiels de RIOS avaient une bonne variabilité et une fiabilité forte. Les données suggèrent que les cinq éléments essentiels pourraient être condensés en trois sous‐échelles, deux d'entre elles ayant fait preuve d'un changement important au fil du temps. Les sous‐échelles d'Ouverture de Soi ont fait preuve d'une validité simultanée avec des mesures auto‐rapportées de la RSC qui existaient déjà. Les résultats suggèrent que RIOS est prometteuse en tant que mesure qui pourrait contribuer à une base factuelle plus rigoureuse pour la pratique de la RSC. Zusammenfassung: Messung der Reflexion in reflektierten Supervisions‐/Beratungssitzungen: Eine erste Validierung der „Reflective Interaction Observation Scale" (RIOS) Die Forschung zu reflektierter Supervision und reflektierter Beratung (reflective supervision/ consultation; RSC) ist begrenzt und stützte sich bislanf in erster Linie auf Selbstberichte und qualitative Interviews. Unseres Wissens gibt es derzeit keine Maße, um das Geschehen während einer RSC‐Sitzung durch Beobachtung zu erfassen. Daher wurde die „Reflective Interaction Observation Scale" (RIOS) entwickelt, um die Qualität von RSC objektiver messen zu können. Ziel diese Studie war es, erste Belege für die Reliabilität und Validität der RIOS zu erbringen. Dies geschah mithilfe einer Stichprobe von Mitarbeitenden der Jugendhilfe (N = 40), die an sechs Online‐Gruppenreflexionsberatungen teilnahmen und nach der ersten und der letzten Sitzung Selbstauskunftsbögen ausfüllten. Der RIOS wurde verwendet, um die erste und letzte Sitzung zu kodieren, die jede:r Teilnehmende besucht hatte. Die Ergebnisse zeigten, dass die wesentlichen Elemente (Essential Elements) der RIOS in dieser Stichprobe eine gute Variabilität und starke Reliabilität aufwiesen. Die Daten legen nahe, dass die fünf wesentlichen Elemente in drei Subskalen zusammengefasst werden können, von denen zwei eine signifikante Veränderung über die Zeit zeigen. Die Subskala Selbstoffenheit zeigte Übereinstimmungs‐Validität mit bereits bestehenden RSC‐Selbstberichtsmaßen. Die Ergebnisse deuten darauf hin, dass die RIOS ein vielversprechendes Maß ist, das einen Beitrag zu einer strengeren Evidenzbasis für die Praxis der RSC leisten könnte. 抄録: リフレクティブ・スーパービジョン/コンサルテーションセッションにおける内省の測定:内省的相互作用観察スケール (RIOS) の初期検証 リフレクティブ・スーパービジョンとリフレクティブ・コンサルテーション (RSC) に関する研究は限定的で、主に自己報告法と質的インタビューに拠ってきた。私たちの知る限り、RSCセッションにおいて何がおきるのかを観察的に測定する方法となる手法は現在のところない。したがって、内省的相互作用観測スケール (RIOS) は、RSCの質をより客観的に測定する手法として生み出された。本研究は、6つのオンライングループリフレクティブコンサルテーションセッションに参加し最初と最後のセッション後に自己申告調査を完了した児童福祉士 (N = 40) のサンプルを通して、RIOSの信頼性と妥当性に関する初期エビデンスを提示することを目的としている。RIOSは、各参加者が参加した最初と最後のセッションをコーディングするために使用された。その結果、このサンプルにおいて、RIOS必須要素は良好な変動性と強い信頼性を示した。データは、5個の必須要素を3個の下位尺度に凝縮できることを示唆しており、そのうちの2個は時間の経過とともに大きな変化を示した。自己開示性下位尺度は、RSCの既存の自己報告法と併存的妥当性を示した。結果として、RIOSは、RSCの実践のためのより厳密な根拠となりうる有望な手法であることが示された。 摘要: 关于反思性监督与反思性咨询 (RSC) 的研究是有限的, 主要依赖于自我报告测量和定性访谈。据我们所知, 目前还没有任何措施可以提供一种方法来观察测量RSC会话期间发生的情况。因此, 反射互动观察量表 (RIOS) 被创建用来更客观地衡量RSC的质量。本研究试图通过儿童福利工作者 (N = 40) 的样本提供关于RIOS信度和效度的初步证据, 他们参加了六次在线小组反思性咨询会议, 并在第一次和最后一次会议后完成了自我报告调查。RIOS被用来编码每个参与者参加的第一次和最后一次会议。结果表明, 在该样本中, RIOS基本要素具有良好的变异度和很强的信度。数据表明, 这五种基本要素可以浓缩成三个分量表, 其中两个分量表随着时间的推移发生了显著变化。自我开放性分量表与已有的RSC自我报告量表具有共时效度。结果表明, RIOS作为一项测量措施, 有助于为RSC实践提供更严格的证据基础, 显示出良好的前景。 ملخص: قياس التأمل في جلسات الإشراف/التشاور التأملي: التحقق الأولي من مقياس رصد التفاعل التأملي (RIOS) الأبحاث المتعلقة بالإشراف والتشاور التأملي محدودة وتعتمد أساسا على مقاييس الإبلاغ الذاتي والمقابلات النوعية. وعلى حد علمنا، لا توجد حالياً مقاييس توفر طريقة لقياس ما يحدث أثناء جلسة الإشراف/ التشاور التأملي. وفي هذا السياق، تم إنشاء مقياس رصد التفاعل التأملي كوسيلة لقياس جودة جلسات الإشراف/ التشاور التأملي بشكل أكثر موضوعية. هدفت هذه الدراسة إلى تقديم أدلة أولية حول موثوقية وصحة هذا المقياس (RIOS) من خلال عينة من العاملين في مجال رعاية الطفل (N = 40) الذين شاركوا في ست جلسات تشاور تأملية جماعية على الإنترنت وأكملوا دراسات استقصائية للإبلاغ الذاتي بعد دورتهم الأولى والأخيرة. وقد استخدم هذا النظام في ترميز الجلسة الأولى والأخيرة التي حضرها كل مشارك. وأظهرت النتائج أن العناصر الأساسية في هذه العينة كانت لها تباينات جيدة وموثوقية قوية. وتشير البيانات إلى أن العناصر الأساسية الخمسة يمكن دمجها في ثلاثة مقاييس فرعية، أظهر اثنان منها تغيرا كبيرا مع مرور الوقت. وأظهر المقياس الفرعي للانفتاح الذاتي صحة متزامنة مع مقاييس الإبلاغ الذاتي القائمة للإشراف/ التشاور التأملي. وتشير النتائج إلى أن مقياس ملاحظة التفاعل التأملي (RIOS) يمكن أن يسهم في تكوين قاعدة أدلة أكثر دقة في ممارسة الإشراف/ التشاور التأملي.